Un approccio al fenomeno editoriale dell’almanacco di corte e la guida della città in Italia, Spagna e Portogallo nel Diciottesimo secolo (ACME, 2023)
The court almanac and the handbook – also known as the «foreigner’s guide» – represent one of the most remarkable derivations of 18th century European almanacs in terms of its variety and consolidation over time. This research seeks to investigate the European origins of this particular publishing segment, focusing on its derivations in the context of southern Europe, particularly in Spain, Portugal and the Italian states. The main objective is to highlight the similarities between Spanish, Portuguese and Italian production in the 18th century, taking into account editorial and textual criteria. At the same time, this study also aims to highlight the specific characteristics of the court almanac and the handbook in each of the states, in order to draw as complete a portrait of this typographic object as possible.